2018
DOI: 10.1159/000491892
|View full text |Cite
|
Sign up to set email alerts
|

Monocrotaline Suppresses RANKL-Induced Osteoclastogenesis In Vitro and Prevents LPS-Induced Bone Loss In Vivo

Abstract: Background/Aims: Extensive osteoclast formation plays a critical role in bone diseases, including rheumatoid arthritis, periodontitis and the aseptic loosening of orthopedic implants. Thus, identification of agents that can suppress osteoclast formation and bone resorption is important for the treatment of these diseases. Monocrotaline (Mon), the major bioactive component of crotalaria sessiliflora has been investigated for its anti-cancer activities. However, the effect of Mon on osteoclast formation and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…[4][5][6]15 Currently, the major modalities used in these diseases treatment, including bisphosphonates, 27 denosumab, 28 and selective estrogen receptor modulators. [4][5][6]15 Currently, the major modalities used in these diseases treatment, including bisphosphonates, 27 denosumab, 28 and selective estrogen receptor modulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6]15 Currently, the major modalities used in these diseases treatment, including bisphosphonates, 27 denosumab, 28 and selective estrogen receptor modulators. [4][5][6]15 Currently, the major modalities used in these diseases treatment, including bisphosphonates, 27 denosumab, 28 and selective estrogen receptor modulators.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 M-CSF stimulates osteoclast proliferation, whereas RANKL is important for the formation of multinuclear giant osteoclasts. 15 Nowadays, many studies have indicated that several compounds derived from natural products promote bone formation by advancing osteoblast differentiation and suppressing the signal pathways for osteoclast formation. Then, TRAF6 stimulates downstream signaling pathways, such as NF-ÎșB signaling pathways.…”
mentioning
confidence: 99%
“…After micro-CT analyses, the calvarias samples were decalcified for 2 weeks in 10% EDTA. Then, paraffin-embedded histopathological sections were used for TRAcP staining, hematoxylin and eosin (H&E) staining, and immunohistochemical staining as previously described (Song et al, 2017;Wei et al, 2018). The TRAcP-positive osteoclasts were determined by ImageJ software.…”
mentioning
confidence: 99%
“…OCs are the only cells in the human body that undergo bone resorption; inhibiting their differentiation and formation can effectively inhibit bone loss and bone dissolution (Wei, Su, et al, ). The results of the experiments carried out in this study demonstrated that Vac could inhibit the differentiation and formation of OCs in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%